Effects of Propolis and Hypericum perforatum Cream on Burn Wound Healing - Durmuş, Ali Said; Han, Mehmet Cengiz; Sağlıyan, Aydın; Özkaraca, Mustafa; Kandemir, Fatih Mehmet (My University, 2018)
This study aimed to evaluate the effects of Propolis (Pr) and Hypericum perforatum (HP) cream ona number of biochemical and histopathological parameters in burn wounds in a rat model. Fortytwo female 3-month-old Wistar Albino rats were assorted into three equal main groups. Each ofmain groups was assorted into two subgroups for postoperative 7 and 14 days follow-ups.Bilaterally 10 mm in diameter second degree thermal burn wounds were created on the back skinof all rats under general anaesthesia. The burned skin areas in the first, second and third groupswere coated with placebo cream (control), 50% Pr cream, and 50% HP cream twice a day,respectively (n= 14 for each group). The rats that completed postoperative follow-up periods of 7and 14 days were euthanized and skin samples were examined biochemically and histologically.Results showed that Pr had more antioxidant property than the other groups. Pr and HP increasedthe burn wound healing effect with its encouraging property for epithelisation and granulation tissueand collagen (P<0.05). In conclusion, local application of 50% Pr cream and 50% HP cream aresignificantly efficacious in healing of burn wounds.
Keywords: Tamamlayıcı ve Entegre Tıp; Dermatoloji; Veterinerlik; Cerrahi